Where has the advocacy gone? : the impact of neoliberalism on community-based social workers' ethical responsibility in the age of risk and vulnerability : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Social Policy at Massey University, Manawatū, New Zealand - Renau, Darren (Massey University, 2021)
Advocacy is fundamental to social work and forms part of a social worker's ethical responsibilities. As part of these responsibilities, it is a requirement for social workers to understand structures and power bases which sustain social injustices. Over the past thirty years, neoliberalism has changed societal attitudes towards people in need of social support. The nature of social work practice has changed too, with advocacy primarily carried out at the micro level. This qualitative-exploratory study aimed to understand how neoliberalism impacted on the ability of social workers to provide support and advocacy to disadvantaged people. It sought to understand community-based social workers' views about neoliberalism and their accounts of how it has changed their practice. Within this environment, the research explored social workers' understanding of advocacy and opportunities for how social workers might extend their advocacy in a neoliberal environment. Using thematic analysis with a social constructionist framework, the research found that social workers have limited understanding of neoliberalism; are placing themselves at risk of sustaining neoliberalism and engaging in 'othering' discourses towards their clients. While social workers are wanting to meet the needs of clients, they are working at an individual level in a way which reinforces neoliberal messaging of self-responsibility and personal initiative. Social workers identify change as possible within their local communities but require greater leadership to engage in this advocacy. Further research into social workers' understanding of neoliberalism and how this impacts their worldview would offer further insight about their capacity to engage in social change. Finally, research into the leadership of social work associations and their perceived value by social workers would help explore the potential of critical reflection and coalesced leadership around community-level social advocacy.
Keywords: 440999 Social work not elsewhere classified